Systematic literature review: STEM integrated biology learning based on 21st century learning models - Devi Mayuko Saragih; Slamet Suyanto; Nasrianus Sera; Sarah Rapma Kristina Sitanggang (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
Science, Technology, Engineering, and Mathematics (STEM) is an integrated approach in the 21st century that aims to develop learners' soft skills and form human resources through 4C skills, namely critical thinking, creative, innovative, communicative and collaborative where the learning process is based on real-life problems. The STEM approach combined with the 21st century learning model can help students in optimising learning outcomes and forming character as human resources with 4C skills. This study aims to examine STEM-integrated biology learning in Problem-Based Learning (PBL) and Project-Based Learning (PjBL) learning models and provide an overview of education in the STEM approach over the past decade at all levels of education in Indonesia. This research used a systematic literature review (SLR) method adapted from the PRISMA model. The results of this study reveal some interesting facts and findings related to the STEM approach in PBL and PjBL models, that student skills and learning outcomes also affect the approach, model and learning media used in biology learning. STEM integration is able to overcome problems in learning biology through scientific phenomena and real-world applications that support the learning process. This research suggests developing and deepening findings in the field of STEM biology in order to achieve optimal, quality and relevant learning outcomes by harmonising the demands of future scientific and technological developments.Abstrak. Science, Technology, Engineering, and Mathematics (STEM) merupakan pendekatan terintegrasi di abad 21 yang bertujuan untuk mengembangkan soft skill peserta didik dan membentuk sumber daya manusia melalui kecakapan 4C yaitu berpikir kritis, kreatif, inovatif, komunikatif dan, kolaboratif dimana proses pembelajarannya berbasis masalah dalam kehidupan nyata. Pendekatan STEM yang dipadukan dengan model pembelajaran abad 21 dapat membantu peserta didik dalam mengoptimalisasi hasil belajar dan membentuk karakter sebagai sumber daya manusia dengan kecakapan 4C. Penelitian ini bertujuan untuk mengkaji pembelajaran biologi terintegrasi STEM dalam model pembelajaran Problem-Based Learning (PBL) dan Project-Based Learning (PjBL) serta memberikan gambaran pendidikan dalam pendekatan STEM selama satu dekade terakhir pada semua jenjang pendidikan di Indonesia. Penelitian ini menggunakan metode tinjauan literatur sistematis (SLR) yang diadaptasi dari model PRISMA. Hasil kajian ini mengungkapkan beberapa fakta dan temuan menarik terkait pendekatan STEM dalam model PBL dan PjBL, bahwa keterampilan dan hasil belajar siswa turut berpengaruh pada pendekatan, model hingga media pembelajaran yang digunakan dalam pembelajaran biologi. Integrasi STEM mampu mengatasi permasalahan dalam pembelajaran biologi melalui fenomena ilmiah dan aplikasi dunia nyata yang menunjang proses pembelajaran. Penelitian ini menyarankan untuk mengembangkan dan memperdalam temuan di bidang biologi STEM agar tercapainya hasil belajar yang optimal, berkualitas dan relevan dengan menyelaraskan tuntutan perkembangan ilmu pengetahuan dan teknologi yang akan datang.